L'Arnau de Vilanova presentat per Francesc Eiximenis. - PIQUER, JOAN REQUESENS I. (Scripta, 2024)
This study is based on a passage by Francesc Eiximenis in his work Primer Llibre del Crestià which, due to an almost one-hundred-year-old error, has led to an altered image of the doctor Arnau de Vilanova. Based on ms. 456 of the Biblioteca de Catalunya and Lambert's Palmart incunabulum printed in València in 1483. Here is studied which was and why the franciscan's choice of comparing Arnau considered as an alchemist in opposition to the king Salomon.